(3GdaJM GdehGgHi aj JQLeI GdTGWHis - (3egfG Hf SfGf Hf YHO GdhgGH GdMSjfjs ((3UMQGA bQH GSOGQ s)
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd HaVdI ef GNJGQ ef ChdjGFg GdebQHjf hHYO agPg efMI ef GdaJM GdehGgHi JfHF Yf deMI ef SjQI CHj GdbGSe GdTGWHi s
(3BNQgG (B:s
(3Jdc GdSYGOI Ef Jde HSGMJgG aMW QLdc bO YhajJ ef faS gPG BNQ eG ef Gddg Hg ef ajV GdecGQe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs